Navigating AI in Producing Cohesion Devices in the Preparatory Paragraph of the Essay - Maisa, M; Agustien, Najwa Septya; Fanany, Syarla Salsabilla; Wirabhakti, Agus; Kereibayeva, Aigerim (Studies in Learning and Teaching, 2025)
Even though technology is the subject of numerous studies, none of them have systematically investigated the upgrading of technology skills in navigating AI to produce cohesion devices, especially in preparatory paragraphs in writing in the ELT context. The investigative approach employed in this study utilized qualitative descriptive methods with thematic and written discourse analysis. The aim of the research is to find out how the teacher students navigate the AI in creating Cohesion Devices in the Preparatory Paragraph of the Essay. The data for this study comprised introductions extracted from the final project essays of English Department undergraduate students during the academic year of 2020-2021. The findings of this study imply that students are less exposed to diverse AI-supported writing because they only integrate ChatGPT, Grammarly, Quilbot, and DeepL AI writing tools in their essays. Students found themselves indirectly using AI, but they also used their critical thinking skills. Brainstorming, Structured Questioning, Idea Selection, and Appropriate Choice are the lead indicators to perceive AI Suggestion adaptation.